Estimation Urinary Tract Infection in Obesity Patients - Wathiq Essam Hameed (Journal of Global Pharma Technology, 2018)
Obesity is representing a global epidemic disease that causes by different factors like environmental, hereditary, medical disease antipsychotic drugs and steroids. Obese people are at high risk to develop many complications such as hypertension, diabetes, atherosclerosis, joints problems, cancers especially hormone dependent, respiratory problems and urinary tract infection and others. To show the association between urinary tract infection and obesity. Eighty-eight people were included in this study about 40 healthy peoples and 48 obese, Uren and data were collected from patients and control to detected urinary tract infection and this gropes classified according to degree of infection into mild, moderate and sever. The results show the urinary tract infection increase in obese people than non-obese. The results of this study support the evidence that obesity associated with urinary tract infection and urinary tract dysfunction is frequently associated with changes in body weight and composition.Key words: Obesity, UTI.